Student Scientific Conference MUNI Pharm 2021: The Book of Abstracts - Bryja, Václav; Poláková, Martina; Robošová, Lucie; Dupľáková, Miriama; Jurčová, Nikol; Crha, Tomáš; Žáčková, Radka; Greguš, Michal; John, Petr; Burclová, Zuzana; Porostlá, Veronika; Hulková, Veronika; et al. (Masaryk University Press, 2021)
The Abstract Book is issued annualy on the occasion of the Student Scientific Conference. It consists of the scientific research project abstracts in the field of pharmacy, which are submitted and presented by the students and evaluated by the scientific committee.